2004
DOI: 10.1194/jlr.m300520-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of HDL-C and cholesteryl ester transfer protein gene mutations and the risk of coronary heart disease in the elderly

Abstract: High density lipoprotein cholesterol (HDL-C) levels are inversely associated with the incidence of coronary heart disease (CHD) in middle-aged individuals; in the elderly, the association is less clear. Genetic factors, including variations in the cholesteryl ester transfer protein (CETP) gene, play a role in determining HDL-C levels. Controversy remains about whether CETP deficiency and the resultant rise in HDL-C are antiatherogenic, or whether CETP has the opposite effect due to its role in reverse choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
108
3
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(119 citation statements)
references
References 44 publications
6
108
3
2
Order By: Relevance
“…Furthermore, the high HDL-C category (1.56 -2.06 mmol/L) showed significant inverse association with CHD mortality; however, the very high HDL-C category ( ≥ 2.07 mmol/L) did not show significant relationship with CHD. Consequently, there is no inverse relationship between HDL-C levels and cardiovascular mortality because major subtype of CVD in Japan is stroke 13,23) ; in fact, the proportion of stroke within CVD (39%) was twice as large as that of CHD (21%) in the present study.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Furthermore, the high HDL-C category (1.56 -2.06 mmol/L) showed significant inverse association with CHD mortality; however, the very high HDL-C category ( ≥ 2.07 mmol/L) did not show significant relationship with CHD. Consequently, there is no inverse relationship between HDL-C levels and cardiovascular mortality because major subtype of CVD in Japan is stroke 13,23) ; in fact, the proportion of stroke within CVD (39%) was twice as large as that of CHD (21%) in the present study.…”
Section: Discussionmentioning
confidence: 69%
“…As mentioned above, in Japan, stroke mortality is much higher than CHD mortality 13,23) , and to our knowledge, almost all Japanese cohort studies did not show any positive relationship between TC or LDL-C and cerebral infarction 24,25) . Even in a large worldwide pooled analysis 26) , a weak positive relationship between TC or LDL-C and stroke was only observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigations of both monogenic CETP deficiency and polymorphisms in the CETP gene provided controversial evidence. Some studies reported reduced cardiovascular disease risk and prolonged life expectancy in individuals with CETP mutants, [193][194][195][196] others did not find any impact or even increased cardiovascular risk. 197,198 Previous meta-analyses of genetic studies, provided compelling evidence that polymorphisms that are associated with reduced CETP activity and increased HDL-cholesterol levels are also associated with reduced cardiovascular risk.…”
Section: Fibratesmentioning
confidence: 98%